The role of silymarin and MAPK pathway in the regulation of proliferation and invasion of non-small cell lung cancer cells: Silymarin’s role in lung cancer cell regulation - Zhang, Jing; Zhang, Kaige; Li, Jing; Zhang, Jia; Cui, Xiaohai (Cellular and Molecular Biology, 2024)
We aimed to explore the role of silymarin and mitogen-activated protein kinase (MAPK) pathway in the regulation of proliferation and invasion of non-small cell lung cancer cells. Non-small cell lung cancer cells were cultured and divided into groups and treated with drugs, and A blank control group was set up. The concentration of silymarin in the experimental group was 10 mg/L, 20 mg/L and 40 mg/L, respectively, which were recorded as groups A, B and C, and three repeated experiments were performed in each group. Absorbance (A value), survival rate and number of invasions were measured at 490 nm 24 h and 48 h after treatment, and the protein expression levels of MMP-2, MMP-9, p-p38, p-JNK and p-ERK 1/2 of cells in each group were detected. There were differences in the A value (control group > Group A > Group B > Group C), cell survival rate (control group < group A < group B < group C) and the number of cell invasions (control group > Group A > Group B > group C) at 24h and 48h among all groups (P<0.05). After 24h of administration, the mRNA expression of MMP-2 and MMP-9, P-P38 and P-JNK protein expression were significantly different among groups, and the control group was > group A > Group B > group C (P<0.05). There were no significant differences in protein expression levels of p38, JNK, ERK 1/2 and P-ERK 1/2 among all groups (P>0.05). Silymarin may inhibit the proliferation and invasion of non-small cell lung cancer cells by inhibiting the activity of MAPK pathway, and the higher the concentration, the more obvious the inhibition effect, which provides a basis for further research and treatment of non-small cell lung cancer.